The prevalence of motility-related genes within the human oral microbiota - Sofia T. Rocha; Dhara D. Shah; Qiyun Zhu; Abhishek Shrivastava (Microbiology Spectrum)
ABSTRACT The human oral and nasal microbiota contains approximately 770 cultivable bacterial species. More than 2,000 genome sequences of these bacteria can be found in the expanded Human Oral Microbiome Database (eHOMD). We developed HOMDscrape, a freely available Python software tool to programmatically retrieve and process amino acid sequences and sequence identifiers from BLAST results acquired from the eHOMD website. Using the data obtained through HOMDscrape, the phylogeny of proteins involved in bacterial type 9 secretion system (T9SS)-driven gliding motility, flagellar motility, and type IV pilus-driven twitching motility was constructed. A comprehensive phylogenetic analysis was conducted for all components of the rotary T9SS, a machinery responsible for secreting various enzymes, virulence factors, and enabling bacterial gliding motility. Results revealed that the T9SS outer membrane β-barrel protein SprA of human oral bacteria underwent horizontal evolution. Overall, we catalog motile bacteria that inhabit the human oral microbiota and document their evolutionary connections. These results will serve as a guide for further studies exploring the impact of motility on the shaping of the human oral microbiota.IMPORTANCEThe human oral microbiota has been extensively studied, and many of the isolated bacteria have genome sequences stored on the human oral microbiome database (eHOMD). Spatial distribution and polymicrobial biofilms are observed in the oral microbiota, but little is understood on how they are influenced by motility. To bridge this gap, we developed a software tool to identify motile bacteria from eHOMD. The results enabled the cataloging of motile bacteria present in the oral microbiota but also provided insight into their evolutionary relationships. This information can guide future research to better understand how bacterial motility shapes the human oral microbiota.